The impact of financial performance to effective tax rates in banking companies on the indonesia stock exchange - Yusnaini; Fitri Handayani; Latersia Gurusinga; Hermawan Sutanto (Jurnal Mantik, 2024)
This research aims to determine the effect of company financial performance as seen from the profitability ratio and fixed asset intensity on effective tax rates in banking companies listed on the IDX for the 2017-2021 period. The type of research used in this research is quantitative research. The population used in this research is all banking companies listed on the Indonesia Stock Exchange in the 2017-2021 period with a research sample of 25 companies. The data analysis technique used in this research is panel data analysis using the E-views version 13 program. The results of the research show that profitability has no effect on the effective tax rate, meanwhile fixed asset intensity has a positive and significant effect on the effective tax rate in banking companies listed on the IDX for the 2017-2021 period